The role and assembly mechanism of nucleoprotein in influenza A virus ribonucleoprotein complexes. - Turrell, L; Lyall, J; Tiley, L; Fodor, E; Vreede, F (2013)
The nucleoprotein of negative-strand RNA viruses forms a major component of the ribonucleoprotein complex that is responsible for viral transcription and replication. However, the precise role of nucleoprotein in viral RNA transcription and replication is not clear. Here we show that nucleoprotein of influenza A virus is entirely dispensable for replication and transcription of short viral RNA-like templates in vivo, suggesting that nucleoprotein represents an elongation factor for the viral RNA polymerase. We also find that the recruitment of nucleoprotein to nascent ribonucleoprotein complexes during replication of full-length viral genes is mediated through nucleoprotein-nucleoprotein homo-oligomerization in a 'tail loop-first' orientation and is independent of RNA binding. This work demonstrates that nucleoprotein does not regulate the initiation and termination of transcription and replication by the viral polymerase in vivo, and provides new mechanistic insights into the assembly and regulation of viral ribonucleoprotein complexes.